Geotechnical characterization of the silt from the terrace of the municipality of Olaya in Antioquia, Colombia (2016)
In April of 2014 arose a movement mass of soils which make up the terrace of the municipality of Olaya (Department of Antioquia). This document presents the results of characterization physical, mechanical and hydro-mechanical behavior of silty soils in such training, in order to evaluate the possible causes of the movement. Were confronted the hypothesis raised by the competent entities that once evaluated the problem and was determined from this research that the soil, for the conditions on the ground, experiences an apparent cohesion as a result of the generation of pore pressures negative, however, when the material comes in contact with water, this cohesion is lost quickly leads to the shear resistance of the material only depend on the angle of internal friction.